2018
DOI: 10.3892/mmr.2018.8790
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑22 inhibits the proliferation and migration, and increases the cisplatin sensitivity, of osteosarcoma cells

Abstract: Osteosarcoma (OS) is the major type of primary bone tumor and is associated with a poor prognosis due to chemotherapy resistance. Accumulating evidence indicates that microRNAs (miRNAs/miRs) may influence the tumor progression of OS and cell sensitivity to chemotherapy. In the present study, a total of 7 patients with OS and 7 healthy volunteers were recruited. Reverse transcription-quantitative polymerase chain reaction and ELISA were performed to determine the expression of miRNAs and mRNAs in the serum of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…17 In osteosarcoma, miR-22 inhibits biological functions and increases cisplatin sensitivity via targeting S100A11. 18 Here, we examined the function of miR-22 in CRC and found that it had a tumorinhibiting role, consistent with the results of other studies. We also showed that miR-22 repressed CRC cell proliferation, migration, and invasion in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…17 In osteosarcoma, miR-22 inhibits biological functions and increases cisplatin sensitivity via targeting S100A11. 18 Here, we examined the function of miR-22 in CRC and found that it had a tumorinhibiting role, consistent with the results of other studies. We also showed that miR-22 repressed CRC cell proliferation, migration, and invasion in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported potential functions of miR-22 in various cancers, including CRC 17 and osteosarcoma. 18 In CRC, miR-22 suppresses cell proliferation and migration in vitro and in vivo by targeting HuR. 17 In osteosarcoma, miR-22 inhibits biological functions and increases cisplatin sensitivity via targeting S100A11.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that MiR‐22 functions as a tumor suppressor in different malignancies, such as prostatic, breast, and gastric cancers. Furthermore, miR‐22 was appreciably decreased in OS patients while its overexpression could suppress MG‐63 cells from dividing and metastasizing. However, the role of miR‐22 and the underlying mechanism in regulating OS and chemoresistance are hitherto unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A study uncovers that miR-630 inhibits OS cell proliferation, which may offer a new mechanism underlying the initiation and progression of OS [28]. Similarly, another study scheduled by Zhou, X et al demonstrates that miR-22 may be a promising therapeutic target and a part of a combination treatment alongside chemotherapeutic agents for OS [29]. Our results unveiled that low expression of miR-455-3p was associated with a poor survival rate of patients, indicating the miR-455-3p might function as tumor suppressor in OS.…”
Section: Discussionmentioning
confidence: 98%